ANALYSIS OF LOCATION AND DECISION-MAKING OF FLEET VEHICLE TYPE WITH CVRP MULTI TRIP AND GRAVITY LOCATION MODEL FOR OPERATIONAL COST EFFICIENCY (Case Study CV. XYZ, Wonoayu-Sidoarjo) - Nofan Hadi Ahmad; Tri Novita Sari; Ari Pranata Primisa Purba (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2023)
Transportation has an important role in the logistics of a company, both in services and products. Increased orders in 2020 for wooden speaker products at CV. XYZ (Wonoayu-Sidoarjo) makes this company try to minimize transportation costs at their operational level. This study focuses on determining the relationship between changes in the type of fleet vehicle and the depot location on the operational costs of product delivery and the time to return to the depot in terms of adding trips. The methodology used in this study is the CVRP Multi Trip with Heterogeneous fleet vehicle and the Gravity Location Model based on the heuristic method. Saving heuristic method and nearest neighbor are heuristic methods used in computational studies to determine the order of visits to the formed sub-routes. There are 4 scenarios that are modeled to further analyze the results of these computations, namely: (1) CVRP multi-trip of old location with wings box truck, (2) CVRP multi-trip of old location with Fuso truck, (3) CVRP multi-trip of the new location with wings box truck, and (4) CVRP multi-trip of the new location with fuso truck. The results of the study concluded that there is a relationship between: (1) changes in fleet vehicle type with total traveling distance, (2) changes in depot location with total traveling distance, (3) fuel consumption rate on vehicle operating costs, (4) average vehicle speed on the time back to the depot. Scenario 4 is the best scenario in terms of traveling distance, fuel costs and delivery time. However, moving the depot center is not easy, so the scenario 2 is the most applicable condition considering that the fuso truck is available and has a higher utility than the wings box truck